State-of-the-art recycling plant. - Perry, T.S (IEEE spectrum)
Consumer electronics giant Matsushita has opened up the METEC (Matsushita Eco Technology Center Company) recycling plant in Japan. The center, the largest of its kind in Japan, opened in 2001 in response to Japan's new law for recycling specific kinds of home appliances. The Hyogo plant recycles all four appliances specified in the law: television sets, refrigerators, air conditioners, and washing machines. For the most part, it recycles these products in kind-that is, crushed glass from TV tubes is used to make new TV tubes; reprocessed plastic from refrigerators is used to make parts for new refrigerators; metals from air conditioner compressors are used to make new compressors; and polypropylene from washing machines is extracted from the other plastics and used to make the bases of new washing machines.